STUDY OF MICROBIAL POLLUTION IN THE ACEH COASTAL WATERS AND ITS VICINITY - Kunarso, Djoko Hadi (Marine Research in Indonesia, 2008)
Study of microbial pollution in the Aceh coastal waters and its vicinity were carried out in the period of August - September 2006. The purpose of the study is to monitor the marine and coastal environments related to the bacterial condition in Aceh waters after the tsunami disaster. The sediment and water samples were collected from 28 stations in four sites in the Aceh waters (Eastern Aceh, Northern Aceh, Western Aceh and Simeulue Islands waters), using the RV. Baruna Jaya VIII. The determination of microbial pollution was based on parameters of coliform and pathogenic bacteria. The coliform bacteria was analysed by membrane filter technique and pathogenic bacteria (Salmonella and Vibrio) by isolation method based on the selective culture media of Salmonella and TCBS agar. The results of the study showed that density of total coliform bacteria varied between 40 and 1055 CFU/100 ml with an average of 443 CFU/100 ml. Based on the pattern of the distribution of coliform bacteria it was found the highest number in Eastern Aceh with the value of 611 CFU/100 ml and the lowest number in Western Aceh with the value of 348 CFU/100 ml. Based on the density of coliform bacteria, Aceh waters was in the lower permissible level of the Indonesian and WHO standards, means that the coastal environment in Aceh waters is still in good condition. Four genera of pathogenic bacteria isolated from seawater samples were Pseudomonas, Citrobacter, Aeromonas and Proteus, and 6 genera from sediments samples were found i.e. Pseudomonas, Citrobacter, Aeromonas, Yersinia, Proteus and Vibrio. The pathogenic bacteria from the samples such as Salmonella typhy and Vibrioparahaemoliticus had low pathogenic potential. This indicated that the risk of pathogenic bacterial contamination in Aceh and its vicinity waters were relatively low, therefore, the conditions of coastal and marine environments were relatively in good condition.